The impact of COVID-19 pandemic on hand hygiene performance in hospitals - Moore, Lori D.; Robbins, Greg; Quinn, Jeff; Arbogast, James W. (American journal of infection control, 2021)
•Hand hygiene opportunities and events decreased as COVID-19 progressed.•Hand hygiene performance initially increased at the outset of the COVID-19 crisis.•Improvements in hand hygiene performance during COVID-19 were not sustained.•Over 35 million hand hygiene opportunities were captured with automated monitoring. Achieving high levels of hand hygiene compliance of health care personnel has been an ongoing challenge. The objective of this study was to examine the impact of the COVID-19 pandemic on hand hygiene performance (HHP) rates in acute care hospitals. HHP rates were estimated using an automated hand hygiene monitoring system installed in 74 adult inpatient units in 7 hospitals and 10 pediatric inpatient units in 2 children's hospitals. A segmented regression model was used to estimate the trajectory of HHP rates in the 10 weeks leading up to a COVID-19-related milestone event (eg, school closures) and for 10 weeks after. Three effects emerged, all of which were significant at P < .01. Average HHP rates increased from 46% to 56% in the months preceding pandemic-related school closures. This was followed by a 6% upward shift at the time school closures occurred. HHP rates remained over 60% for 4 weeks before declining to 54% at the end of the study period. Data from an automated hand hygiene monitoring system indicated that HHP shifted in multiple directions during the early stages of the pandemic. We discuss possible reasons why HHP first increased as the pandemic began and then decreased as it progressed.